2020
DOI: 10.14202/vetworld.2020.2422-2428
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of various step-dilution techniques on the quality of frozen Limousin bull semen

Abstract: Background and Aim: Indonesia has two National Artificial Insemination centers and 17 Regional Artificial Insemination Centers. The frozen semen production techniques differed between the centers, including the type of diluent and semen dilution technique. The aim of the research was to compare the quality of frozen Limousin bull semen diluted using different techniques. Materials and Methods: Semen was collected from three sexually mature Limousin bulls using an artificial vagina. Immediately after collectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
(26 reference statements)
0
13
0
Order By: Relevance
“…The current study showed the effects of different doses of Hesp and two different semen freezing methods on Simmental bulls' sperm characteristics and oxidative stress status. Different cryopreservation methods have been designed to achieve a higher quality of frozenthawed semen (Arif et al, 2020;Jha et al, 2019). The comparison of the one and two-step dilution protocols showed less toxicity for sperm in the two-step dilution because of the slower exposure of sperm to glycerol (Brito et al, 2017); On the other hand, less contamination and easy handling of the one-step dilution method increased this protocol usage in AI stations (Schulze et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study showed the effects of different doses of Hesp and two different semen freezing methods on Simmental bulls' sperm characteristics and oxidative stress status. Different cryopreservation methods have been designed to achieve a higher quality of frozenthawed semen (Arif et al, 2020;Jha et al, 2019). The comparison of the one and two-step dilution protocols showed less toxicity for sperm in the two-step dilution because of the slower exposure of sperm to glycerol (Brito et al, 2017); On the other hand, less contamination and easy handling of the one-step dilution method increased this protocol usage in AI stations (Schulze et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results, there were no significant alterations between the oneand the two-step dilution methods, but higher MDA and AST levels were detected in the threestep compared to the one-step dilution and higher MDA and AST levels in the one-and threestep compared to the two-step dilution. The sperm plasma membrane integrity could not be evaluated perfectly, but there was a significant reduction between the one-and three-step dilutions (Arif et al, 2020). Moreover, fresh boar semen was collected from three European AI centers to assess the one-and two-step dilution methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sperm viability was assessed by mixing 50 µL of semen with 100 µL of eosin nigrosine stain, smeared, and dried at 37 ℃. Examination of the integrity of the sperm plasma membrane was performed by mixing 50 µL of semen with 950 µL of HOS solution (Arif et al, 2020).…”
Section: Sperm Viability and Sperm Plasma-membrane Integrity Assessmentsmentioning
confidence: 99%
“…The most obvious difference between most of protocols is the addition of glycerol before and after cooling during the Chikso cryopreserved semen process. It has been reported that post-thaw motility of bison sperm was not observed significant effects by glycerol addition time (Vilela et al, 2017;Arif et al, 2020). However, other colleage have been showed that sperm motility was altered by glycerol addition time in freezing-thawing Mediterranean buffalo (B.bubalis) sperm (Fabbrocini et al, 2000).…”
Section: Introductionmentioning
confidence: 97%